Valuation of Bonds With Embedded Options - Krchňavý, Martin; Witzany, Jiří, 1966-; Juhászová, Jana; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2018)
The objective of this thesis is to demonstrate the valuation process of a bond with embedded option. Two government fixed-income instruments, one with a call option and the other with a put option, are chosen to avoid credit risk modeling and to keep focus on the option valuation. The value of risk-free callable and putable bonds depends primarily on the evolution of interest rate thus stochastic interest rate models play a major role. Various short-rate models are assumed and represented in lattice structures. Diﬀerent volatility calibration techniques are used accordingly to the available data for each market. Finally, the obtained values are then compared to the actual price observed. The raw data are imported from a trading data platform,transformed using a spreadsheet software, and the pricing algorithm is implemented in a numerical analysis software. Given the nature of option valuation, the basics of stochastic processes are required but the text avoids unnecessary complexity.
Vedoucí práce: Jiří Witzany
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: finanční inženýrství [obor dipl. práce]; diplomové práce; master's theses